“Disadvantaged patient populations”: A theory-informed education needs assessment in an urban teaching hospital - Lindsay Baker; Emilia Kangasjarvi; Beck McNeil; Patricia Houston; Stephanie Mooney; Stella Ng (Canadian Medical Education Journal, 2019)
Recent calls in medical education and health care emphasize equitable care for disadvantaged patient populations (DPP), with education  highlighted as a key mechanism to move toward this goal. However, in order to develop effective education strategies we must first better understand the DPP concept.